SISTEM INFORMASI AKADEMIK BERBASIS WEBSITE PADA SMP ST. BELLARMINUS - Joseline Joseline; Dedi Trisnawarman (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
Junior high school of Saint Bellarminus is a school that has hundreds of students in it and still uses manual systems in conducting academic data collection. Academic data collection with the number of students that much allows the school to feel difficulties in carrying out their duties. The purpose of this application program is to build a web-based information system at SMP St. Bellarminus. This application uses XAMPP as localhost and PhpMyAdmin as Database Manager. This web application functions to search, input, edit, search student data, grades, schedules, attendance and teachers. Students can see directly the value data, schedule and attendance while the teacher can input values and attendance directly into the system through their respective user logins.